Fostering therapeutic security in insecure times: Populism and the new rise of nationalism. Issue 1 (13th January 2022) - Chrząstowski, Szymon
A sense of security is a key issue in attachment theory and its derivation, attachment narrative therapy. This article focuses on an analysis of threats to security that result from the socio-cultural context in which psychotherapy and supervision are conducted. Europe is perceived as a relatively safe place. However, growing populism and nationalism are affecting the context in which psychotherapy is being carried out, by reducing the sense of security of patients, therapists and supervisors alike. The article explores this phenomenon. An example of supervision will be provided, carried out by Arlene Vetere shortly after the brutal murder of a prominent Polish politician. Consideration will be given to the agreement of views between the supervisee and the supervisor, as well as its significance to the supervision. The manner in which security is built within supervision rooted in attachment narrative therapy will also be analysed. The thesis posited is that a sense of security is not an innate personal characteristic but results from actively working towards it and a description of such actions is also offered in the article.